Preliminary survival experiments in transplanting pomegranate - Melgarejo P.; Martínez J.; Martínez J.J.; Sánchez M. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
Pomegranate is usually propagated by rooting hardwood cuttings, which are transplanted to their permanent place after one year in the greenhouse. The cuttings are normally uprooted in winter, while they are usually transferred to the definitive plot between the end of winter and the beginning of spring, always before sprouting, although different factors may intervene to prevent this. We therefore decided to study the latest time it was possible to make this final transplantation, using plants which had rooted in 1997, taken from the greenhouse in December of the same year, kept in cold storage at 5 degrees C and 95-100 per cent relative humidity and planted out at different times in 1998. The results show that this species can be planted out until May (in the ecological conditions of Alicante province) as long as cold storage is adequately carried out.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)